বিশ্ব শিশু পরিস্থিতি ২০০১ / Early Childhood. - United Nations Children's Fund, New York, NY.; United Nations Children's Fund, New York, NY. ([Washington, D.C.] : ঢাকা : Distributed by ERIC Clearinghouse, ইউনিসেফ বাংলাদেশ, 2000)
Although the experiences from birth to age three influence how the rest of childhood unfolds, this critical time is usually neglected in the policies, programs, and budgets of countries around the world. This report details the daily lives of parents and other caregivers who are striving to protect the rights and meet the needs of young children. Section 1 of the report makes the case for investing in the earliest years of childhood, when brain development is most malleable and rights are most vulnerable. This section examines the options governments have concerning where and when to make investments and argues for the importance of early childhood development programs for children, their parents and caregivers, and for national progress. This section further argues that early childcare can be an effective antidote to cycles of violence, conflict, poverty, and HIV/AIDS. The section concludes with descriptions of experiments and experiences in developed and developing nations with informal support networks and community agencies with innovative childcare programs. Section 2 presents three maps illustrating quality of life indicators for early childhood, the link between women's status and children's well-being, and the challenges to children's growth and development. Section 3 presents the latest data on children's well-being for 193 countries listed alphabetically, along with regional summaries and world totals. Countries are first ranked in descending order of estimated 1999 under-five mortality rate, which is then included in each of the following tables: basic indicators, nutrition, health, education, demographic indicators, economic indicators, women, and rate of progress. (Contains 65 reference notes.) (KB)
Availability: UNICEF, UNICEF House, 3 UN Plaza, New York, NY 10017; Web site: http://www.unicef.org; e-mail: pubdoc@unicef.org ($12.95).
ERIC Note: For 1999 report, see ED 426 811.
Microfiche.
Keywords: Children -- Health and hygiene; Child development